2022
DOI: 10.3991/ijet.v17i02.25937
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Workspaces for Enhancing Collaborative Work in EFL Learning: A Case Study in Higher Education

Abstract: Abstract— The purpose of this study was to determine students’ perceptions towards the use of virtual workspaces for enhancing collaborative work in higher education. The participants were 122 (72 graduate and 50 postgraduate) Teaching English as a foreign language (TEFL) students who were enrolled in different courses at a private university in Ecuador. The students’ proficiency levels varied from B1 to C1 according to the Common European Framework of Reference for Languages (CEFR). A mixed-method approach wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…It encourages students to become an independent learner and promotes autonomy where teachers and learners actively and voluntarily engage in the teaching-learning process. Moreover, Castillo-Cuesta et al, [35] article and findings "ICT tools are essential and effective in classroom pedagogy" (p. 11). Li, Z.…”
Section: Discussionmentioning
confidence: 99%
“…It encourages students to become an independent learner and promotes autonomy where teachers and learners actively and voluntarily engage in the teaching-learning process. Moreover, Castillo-Cuesta et al, [35] article and findings "ICT tools are essential and effective in classroom pedagogy" (p. 11). Li, Z.…”
Section: Discussionmentioning
confidence: 99%
“…And interpreting it, sharing information, and building knowledge by relying on collaborative tools and various electronic brainstorming tools that help in developing their thinking skills. It also provides group feedback activities, and this is known as electronic collaborative learning [11].…”
Section: A E-collaborative Learningmentioning
confidence: 99%
“…This study came to reveal the effectiveness of collaborative e-learning in developing digital thinking skills. Although studies [10][11][12][13] confirm the effectiveness of using electronic collaborative learning due to its many advantages, the vast majority of learners do not benefit from the services electronic collaborative learning is largely because it may not meet their needs in a way that suits their learning styles, this due to the fact that electronic collaborative learning environments do not help learners to interact and integrate easily in their preparations, interests and learning style, and to improve digital thinking skills according to electronic collaborative learning requires the adoption of a learning theory that fits with the nature and characteristics of digital skills diploma teachers for the primary stage and their learning styles, such as connectivism theory, which is considered one of the best educational theories in the digital age, as revealed by many studies [2,[14][15][16] which focuses on the use of digital technology in learning based on networks within an effective social framework.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Kosnin et al tested the effectiveness of the Jamboard application on a Financial Management course among students of the Faculty of Hospitality, Tourism, and Wellness and reported that Jamboard was an effective tool for drawing and writing online. Another finding from the research to examine the perceptions of students toward the application of virtual workspace like Jamboard by Castillo-Cuesta et al (2022) revealed that the implementation of Jamboard created the positive learning environment which fostered students' collaborative and communication skills, engagement and active particapation, interest and motivation. Khoiriyah et al (2022) realized from the research of embedding Jamboar to collaborative reading strategies that the Jamboard is beneficial for their study and simple to use.…”
Section: Previous Studiesmentioning
confidence: 99%